Crystal Structure, Hirshfeld Surface Analysis, and Biological Activities of Schiff-Base Derivatives of 4-Aminoantipyrine - Aguilar Llanos, Esteban (2023)
Eight Schiff bases, synthesized by the reaction of 4-aminoantipyrine with different cinnamaldehydes, were studied in the solid state by using vibrational spectroscopy (IR) and X-ray diffraction techniques. The analysis was extended to the solution phase through ultraviolet-vis, fluorescence spectroscopy, and cyclic voltammetry. Finally, the crystal structures of four compounds (3b, 3d, 3g, and 3h) were determined and studied. In addition to the experimental study, theoretical calculations using the semiempirical method PM6/ZDO were performed to understand better the compound’s molecular properties, UV-vis, and infrared spectra. The primary difference is the angular conformation of the terminal phenyl rings around the corresponding linking C-N and C-C σ-bonds. Furthermore, as a result of extended bonding, the > C═N- azomethine group-containing Cpyr-N═(CH)-(CR)═(CH)-Cbz chain (with R═H for 3b, 3d, and 3h, and R═CH3 for 3g) is planar, nearly coplanar, with the mean plane of the pyrazole ring. Hirshfeld surface (HS) analysis was used to investigate the crystal packing and intermolecular interactions, which revealed that intermolecular C-H···O and C-H···N hydrogen bonds, π···π stacking, and C-H···π and C═O···π interactions stabilize the compounds. The energy contributions to the lattice energies of potential hydrogen bonds were primarily dispersive and repulsive. All derivatives were tested in vitro on LPS-stimulated mouse macrophages to assess their ability to suppress the LPS-induced inflammatory responses. Only a slight reduction in the level of NO production was found in activated macrophages treated with 3h. Additionally, the derivatives were tested for antimicrobial activity against several clinical bacteria and fungi strains, including three biofilm-forming microorganisms. Nevertheless, only Schiff base 3f showed interesting antibacterial activities with minimum inhibitory concentration (MIC) values as low as 15.6 μM against Enterobacter gergoviae. On the other hand, Schiff base 3f and, to a lesser extent, 3b and 3h showed antifungal activity against clinical isolates of Candida. The lowest MIC value was for 3f against Candida albicans (15.6 μM). It is interesting to note that the same Schiff bases exhibit the highest activity in both biological evaluations.